Determining dangerous chemicals on the surface of metallic historical artefacts - Vovk, Yuliia; Merezhko, Nina; Indutnyi, Volodymyr; Pirkovich, Kateryna; Lytvynenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2022)
The problem is to determine the threat of chemical damage to a person upon his contact with historical artifacts from metals. For this purpose, experimental studies of the process of accumulation of chemicals on the surface of historical metal products were carried out. The objects of this study were 3 samples of historical cold weapons selected from the museum fund, as well as samples from modern sheet steel. The blades of museum objects were rubbed with a special ash-free swab, which was burned, and the chemical composition of the residue was determined. This makes it possible to obtain data on compounds from a significant surface area. A list of chemical elements that accumulate on the surface of metallic historical artifacts over time has been established. Theoretically, the possibility of the appearance on the surface of historical artifacts made of iron of such chemical elements as Mercury, Barium, Stibium, Phosphorus, Plumbum (Lead), Thallium, Chromium, Selenium, Cadmium has been theoretically proven. This can pose a threat to the health of museum workers and collectors who are in daily contact with such items. The results of the experiment are provided with samples of modern steel, which, in order to accelerate the process of elimination of impurity elements, warmed up for 3 hours in a muffle furnace at a temperature of 700 °C. The surface of these samples was studied using an electron microscope, and local emission analysis of the chemical composition was carried out. The obtained results confirm the process of elimination of ions of individual chemical elements from the metal in the process of its heating. We can observe the release of Al, Si, S, K, Ca, Cu ions to the surface. Based on the results obtained, plots are built that describe the change in the chemical composition of the metal surface throughout the history of existence. The use of the author’s method of testing makes it possible to study the problem of safety of handling historical monuments in general. The results of the study are important for establishing the authenticity of metallic historical artifacts and assessing possible risks in contact with them.